2010
DOI: 10.1002/micr.20787
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience with the delay phenomenon in autologous breast reconstruction with the deep inferior epigastric artery perforator flap

Abstract: In a very select group of patients undergoing breast reconstruction whose DIEP flaps showed vascular compromise before detachment, the delay phenomenon successfully enhanced vascularity and prevented fat necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Preoperative knowledge of flap volume may decrease time spent intraoperatively, sequentially trimming tissue for a better flap fit into the breast pocket. It may also encourage appropriate use of the delay phenomenon for DIEP flaps 20 in patients who are preoperatively determined to have inadequately sized flaps without recruitment of marginal zones.…”
Section: Discussionmentioning
confidence: 97%
“…Preoperative knowledge of flap volume may decrease time spent intraoperatively, sequentially trimming tissue for a better flap fit into the breast pocket. It may also encourage appropriate use of the delay phenomenon for DIEP flaps 20 in patients who are preoperatively determined to have inadequately sized flaps without recruitment of marginal zones.…”
Section: Discussionmentioning
confidence: 97%
“…In this setting, ligating the DIEA and SIEA 1–2 weeks prior to tissue transfer can potentially decrease the rate of partial flap necrosis from as high as 30% to between 5 and 10%, especially in patients with risk factors such as smoking and obesity (Ribuffo etal., 2007). A recent clinical study conducted at Johns Hopkins University has now shown that there are clear benefits to performing surgical delay prior to tissue transfer in improving the viability of DIEP flaps in compromised or unfavorable anatomies (Christiano and Rosson, 2010). As such, a greater understanding of the delay phenomenon in the ITA–DIEA system is important, as it may not only herald the conception of new flap designs, but may also play a key role in improving the dependability of existing flaps, such as the SIEA flap, which is currently limited to a minority of breast reconstruction patients due to a weak and unreliable blood supply, despite its proven advantages in minimizing donor site morbidity (Piorkowski et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…By slightly overcorrecting the amount of medial movement of the cheek, the surgeon will be able to come back and surgically define the medial border of the cheek exactly where it should be after 2 to 3 weeks of initial flap settling (►Figs. 4,5).…”
Section: First Round Of Reconstruction Of Extended Nasal Tip Defectsmentioning
confidence: 98%
“…This is an excellent time to consider adding a delay stage 7 to 10 days prior to flap execution to provide a more robust vascular supply. [4][5][6] Folded forehead flaps: Folded forehead flaps are the modern-day workhorse for full-thickness nasal reconstruction for all of the same reasons that paramedian forehead flaps (PMFF) are the mainstay for complex nasal reconstruction: potential for abundant skin and tissue, axial pattern blood supply, and ability to be shaped and thinned. The folded forehead flap, therefore, provides several advantages for internal lining reconstruction.…”
Section: First Round Of Reconstruction Of Extended Nasal Tip Defectsmentioning
confidence: 99%